1998
DOI: 10.1038/bjc.1998.645
|View full text |Cite
|
Sign up to set email alerts
|

Somatic alterations of the SMAD-2 gene in human colorectal cancers

Abstract: Summary The SMAD-2 gene, which is located at 1 8q21, has been identified as a candidate tumour-suppressor gene from work on colorectal cancers. The aim of the present study was to determine the clinical alterations and the significance of its mutations in a series of colorectal cancers previously examined for SMAD-4/DPC-4 gene. Mutation analyses of the SMAD-2 gene were carried out on cDNA samples from 36 primary colorectal cancer specimens using a combination of the polymerase chain reaction (PCR), single-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Tumor cells often become resistant to TGF-b-induced growth inhibition and apoptosis due to functional inactivation of TGF-b receptors and Smads. Inactivated Smads 2 and 4 have been found due to deletion or mutation in their genes (Hahn et al, 1996;Riggins et al, 1997;Takagi et al, 1998;Schutte, 1999;Blobe et al, 2000;de Caestecker et al, 2000;Massague´and Chen, 2000;Yanagisawa et al, 2000;Derynck et al, 2001;Fink et al, 2001). In contrast to known tumor suppressors Smads 2 and 4, the tumor suppressive role of Smad3 has not been clarified because mutations in the Smad3 gene have thus far not been discovered in human tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells often become resistant to TGF-b-induced growth inhibition and apoptosis due to functional inactivation of TGF-b receptors and Smads. Inactivated Smads 2 and 4 have been found due to deletion or mutation in their genes (Hahn et al, 1996;Riggins et al, 1997;Takagi et al, 1998;Schutte, 1999;Blobe et al, 2000;de Caestecker et al, 2000;Massague´and Chen, 2000;Yanagisawa et al, 2000;Derynck et al, 2001;Fink et al, 2001). In contrast to known tumor suppressors Smads 2 and 4, the tumor suppressive role of Smad3 has not been clarified because mutations in the Smad3 gene have thus far not been discovered in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Smad4, located in 18q21, is also altered in colorectal cancers (Calonge and Massague´, 1999) with a higher incidence of mutation in metastatic colon carcinomas (Schutte, 1999;Fink et al, 2001). Studies have shown a mutated Smad2 gene in colorectal and lung cancers although this gene is a less frequent target than Smad4 gene (Riggins et al, 1997;Takagi et al, 1998;Takenoshita et al, 1998;Yanagisawa et al, 2000). However, to date, there is no evidence that Smad3 is the locus of homozygous deletions, functionally inactivating mutations, or amplifications in human malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The loss or mutation of the Smad4 gene in one allele is often accompanied by a genetic alteration of Smad4 in the other allele. The Smad2 gene has been found mutated in colorectal and lung cancers although this gene is a less frequent target than Smad4 gene (Eppert et al, 1996;Riggins et al, 1996;Uchida et al, 1996;Takagi et al, 1998). Mutations in the Smad3 gene have thus far not been discovered in tumors.…”
Section: Smad Mutations In Cancermentioning
confidence: 99%
“…10 SMAD2 mutations have been found in less than 10% of cases. 11,12 Thus the observed frequency of alterations in the DCC and SMAD genes does not explain the high proportion of chromosome 18q loss in colorectal cancer. This suggests that other tumor suppressor genes, in addition to the DCC and SMAD genes, may be targets for the 18q loss.…”
mentioning
confidence: 92%